Humanisation of a claudin-1-specific monoclonal antibody for clinical prevention and cure of HCV infection without escape. Issue 4 (30th March 2017) - Colpitts, Che C; Tawar, Rajiv G; Mailly, Laurent; Thumann, Christine; Heydmann, Laura; Durand, Sarah C; Xiao, Fei; Robinet, Eric; Pessaux, Patrick; Zeisel, Mirjam B; Baumert, Thomas F
Abstract : Objective: HCV infection is a leading cause of chronic liver disease and a major indication for liver transplantation. Although direct-acting antivirals (DAAs) have much improved the treatment of chronic HCV infection, alternative strategies are needed for patients with treatment failure. As an essential HCV entry factor, the tight junction protein claudin-1 (CLDN1) is a promising antiviral target. However, genotype-dependent escape via CLDN6 and CLDN9 has been described in some cell lines as a possible limitation facing CLDN1-targeted therapies. Here, we evaluated the clinical potential of therapeutic strategies targeting CLDN1. Design: We generated a humanised anti-CLDN1 monoclonal antibody (mAb) (H3L3) suitable for clinical development and characterised its anti-HCV activity using cell culture models, a large panel of primary human hepatocytes (PHH) from 12 different donors, and human liver chimeric mice. Results: H3L3 pan-genotypically inhibited HCV pseudoparticle entry into PHH, irrespective of donor. Escape was likely precluded by low surface expression of CLDN6 and CLDN9 on PHH. Co-treatment of a panel of PHH with a CLDN6-specific mAb did not enhance the antiviral effect of H3L3, confirming that CLDN6 does not function as an entry factor in PHH from multiple donors. H3L3 also inhibited DAA-resistant strains of HCV and synergised with current DAAs. Finally, H3L3 cured persistent HCV infection in human-liver chimeric uPA-SCID mice in monotherapy. Conclusions: Overall, these findings underscore the clinical potential of CLDN1-targeted therapies and describe the functional characterisation of a humanised anti-CLDN1 antibody suitable for further clinical development to complement existing therapeutic strategies for HCV.